Increasing Precipitation Interval Has More Impacts on Litter Mass Loss Than Decreasing Precipitation Amount in Desert Steppe - Qu, Hao; Zhao, Xueyong; Lian, Jie; Tang, Xia; Wang, Xinyuan; Medina-Roldán, Eduardo (Frontiers in Environmental Science, 2020)
Litter mass loss and nutrient release are key links in the material cycling and energy flowing in ecosystems and of special ecological significance in maintaining ecosystem stability, improving soil structure and promoting vegetation restoration in the arid and semi-arid regions. Furthermore, litter mass loss could be affected by the change in precipitation patterns. However, currently, most studies on the response of litter mass loss to precipitation pattern change focus on the precipitation amount much more than the precipitation frequency. Therefore, we conducted a three-year manipulative research in a desert steppe to assess the effects of decreasing precipitation amount and increasing precipitation interval on the litter mass loss of Stipa klemenzii, and their relationships with litter chemical traits (contents of carbon (C), nitrogen (N), phosphorus (P), potassium (K), lignin and ash, C/N ratio and lignin/N ratio) and abiotic factors (light intensity and temperature and humidity of soil and air). The results showed that (1) both the treatments have negative effects on litter mass loss; (2) for abiotic factors, both the treatments only affected soil moisture; for biotic factors, both the treatments decreased the litter lignin contents, the increased precipitation interval treatment decreased the litter N and K contents while increased the litter C/N ratio and lignin/N ratio; (3) the main control of litter mass loss was due to our manipulation of drought regime and its effects on the soil decomposition environment, rather to other factors such as litter quality or light intensity; (4) compare to decreased precipitation amount, increased precipitation interval has more impact on litter mass loss, and this was caused by the increased litter C/N ratio in increased precipitation interval treatment. We speculated that increased precipitation interval was a harsher abiotic factor for the decomposer, and more research on this should be conducted in the future.